2020
DOI: 10.3390/cells9102201
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Gq/11-Mediated Plasma Membrane Translocation of Sphingosine Kinase-1

Abstract: Diverse extracellular signals induce plasma membrane translocation of sphingosine kinase-1 (SphK1), thereby enabling inside-out signaling of sphingosine-1-phosphate. We have shown before that Gq-coupled receptors and constitutively active Gαq/11 specifically induced a rapid and long-lasting SphK1 translocation, independently of canonical Gq/phospholipase C (PLC) signaling. Here, we further characterized Gq/11 regulation of SphK1. SphK1 translocation by the M3 receptor in HEK-293 cells was delayed by expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…It is currently not fully clear whether stimulated platelet S1P release mainly occurs from these intracellular storage pools or also, in part, as a result of elevated SphK activity upon platelet activation, e.g., by the translocation of SphK to the plasma membrane. This has been suggested recently for SphK1 in fibroblasts [ 50 ]. In platelets, SphK2 has been reported as the quantitatively relevant isoform, and the question of whether it is translocated to the plasma membrane upon platelet activation has not yet been resolved.…”
Section: S1p-biosynthesis Release and Functionssupporting
confidence: 62%
“…It is currently not fully clear whether stimulated platelet S1P release mainly occurs from these intracellular storage pools or also, in part, as a result of elevated SphK activity upon platelet activation, e.g., by the translocation of SphK to the plasma membrane. This has been suggested recently for SphK1 in fibroblasts [ 50 ]. In platelets, SphK2 has been reported as the quantitatively relevant isoform, and the question of whether it is translocated to the plasma membrane upon platelet activation has not yet been resolved.…”
Section: S1p-biosynthesis Release and Functionssupporting
confidence: 62%
“…3A). Recently, a direct interaction between activated Gα q/11 proteins and SK1 has been proposed ( 38 ). In line with this, we observed that NK 1 R, H 1 R, and US28 activity enhance the proximity of SK1 and mini-Gα q (fig.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, there are two SphK isoforms, SphK1 and SphK2, with important differences. SphK1 is found in the cytosol, and can translocate to the plasma membrane upon stimulation (Wattenberg et al, 2006;ter Braak et al, 2009;Siow and Wattenberg, 2011;Blankenbach et al, 2020). SphK2 exists in and goes back and forth between the cytosol and nucleus depending on cellular conditions; there are reports of SphK2 in mitochondria and the endoplasmic reticulum as well (Siow and Wattenberg, 2011;Chan and Pitson, 2013;Blankenbach et al, 2020).…”
Section: Sphingolipid Pathwaymentioning
confidence: 99%
“…SphK1 is found in the cytosol, and can translocate to the plasma membrane upon stimulation (Wattenberg et al, 2006;ter Braak et al, 2009;Siow and Wattenberg, 2011;Blankenbach et al, 2020). SphK2 exists in and goes back and forth between the cytosol and nucleus depending on cellular conditions; there are reports of SphK2 in mitochondria and the endoplasmic reticulum as well (Siow and Wattenberg, 2011;Chan and Pitson, 2013;Blankenbach et al, 2020). While both enzymes act primarily on sphingosine and dihydrosphingosine, SphK1 functions with higher catalytic efficiency while SphK2 is capable of inefficiently phosphorylating additional substrates (Liu et al, 2000;Siow and Wattenberg, 2011).…”
Section: Sphingolipid Pathwaymentioning
confidence: 99%